Listeria monocytogenes – How This Pathogen Survives in Food-Production Environments? - Osek, Jacek; Lachtara, Beata; Wieczorek, Kinga (Frontiers in Microbiology, 2022)
The foodborne pathogen Listeria monocytogenes is the causative agent of human listeriosis, a severe disease, especially dangerous for the elderly, pregnant women, and newborns. Although this infection is comparatively rare, it is often associated with a significant mortality rate of 20–30% worldwide. Therefore, this microorganism has an important impact on food safety. L. monocytogenes can adapt, survive and even grow over a wide range of food production environmental stress conditions such as temperatures, low and high pH, high salt concentration, ultraviolet lights, presence of biocides and heavy metals. Furthermore, this bacterium is also able to form biofilm structures on a variety of surfaces in food production environments which makes it difficult to remove and allows it to persist for a long time. This increases the risk of contamination of food production facilities and finally foods. The present review focuses on the key issues related to the molecular mechanisms of the pathogen survival and adaptation to adverse environmental conditions. Knowledge and understanding of the L. monocytogenes adaptation approaches to environmental stress factors will have a significant influence on the development of new, efficient, and cost-effective methods of the pathogen control in the food industry, which is critical to ensure food production safety.